2016
DOI: 10.1002/ceat.201500254
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Physicochemical Parameters of Organic Solutes on the Retention and Flux in a Nanofiltration Process

Abstract: A comparative study of several organic compounds (atrazine, aniline and phenol, and their derivatives, 4-chlorophenol, 4-nitrophenol and 4-nitroaniline) and their removal from aqueous solutions by nanofiltration using an NF-97 polyamide membrane is presented. The aim was to ascertain any correlation between the physicochemical parameters of the different compounds and the characteristic parameters of the nanofiltration system (permeate flux and rejection coefficient), in order to understand the behavior of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…The best correlation for the rejection coefficient was obtained using the molar refractivity and the water solubility of the compound simultaneously. For permeate flux, the best correlation value was obtained using the surface tension and molecular weight [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The best correlation for the rejection coefficient was obtained using the molar refractivity and the water solubility of the compound simultaneously. For permeate flux, the best correlation value was obtained using the surface tension and molecular weight [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other methods include air stripping, ozonation, and advanced oxidation, which all have their own limitations. Membrane technology, therefore, represents an innovation which has the potential for overcoming these limitations .…”
Section: Introductionmentioning
confidence: 99%
“…There are several factors involved in the MWCO determinations when the solute rejection technique is used, e.g., interactions between the solutes/solvent/membrane materials; size, charge, and shape of the molecules; swelling effect; etc. Several studies have been reported in order to establish characteristic parameters of the ultrafiltration (UF) and NF systems, namely, permeate flux and rejection coefficient . From these experimental observations it was clear that the solute rejection was strongly dependent on both the type of solvent and the membrane.…”
Section: Methodsmentioning
confidence: 99%